2022
DOI: 10.3389/fphar.2022.965788
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial near-infrared light in treatment of neurodegenerative diseases

Abstract: Light is a natural agent consisting of a range of visible and invisible electromagnetic spectrum travels in waves. Near-infrared (NIR) light refers to wavelengths from 800 to 2,500 nm. It is an invisible spectrum to naked eyes and can penetrate through soft and hard tissues into deep structures of the human body at specific wavelengths. NIR light may carry different energy levels depending on the intensity of emitted light and therapeutic spectrum (wavelength). Stimulation with NIR light can activate intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…Transcranial or intranasal PBM for brain stimulation with R and NIR light has focused attention on positive outcomes on cognitive functions, the repair of neurodegenerative processes, control of energy metabolism, and adjustment of chronic brain inflammatory processes in AD subjects. Publications of experimental and clinical studies on tPBM in AD and other neurodegenerative disorders and ischemic brain injuries have demonstrated that this modality of therapy stimulates metabolic processes in brain tissue, increases intracellular ATP production and revives neuronal mitochondrial activity; modulates local oxidative stress; favors angiogenesis, capillary and lymphatic revascularization; restores destroyed synapses and generates new synapses; revitalizes the growth of new neural cells and acts as a neuroprotector, thus improving cognitive function and memory [ 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 ].…”
Section: Photobiomodulation Of the Brain And The Treatment Of Alzheim...mentioning
confidence: 99%
“…Transcranial or intranasal PBM for brain stimulation with R and NIR light has focused attention on positive outcomes on cognitive functions, the repair of neurodegenerative processes, control of energy metabolism, and adjustment of chronic brain inflammatory processes in AD subjects. Publications of experimental and clinical studies on tPBM in AD and other neurodegenerative disorders and ischemic brain injuries have demonstrated that this modality of therapy stimulates metabolic processes in brain tissue, increases intracellular ATP production and revives neuronal mitochondrial activity; modulates local oxidative stress; favors angiogenesis, capillary and lymphatic revascularization; restores destroyed synapses and generates new synapses; revitalizes the growth of new neural cells and acts as a neuroprotector, thus improving cognitive function and memory [ 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 ].…”
Section: Photobiomodulation Of the Brain And The Treatment Of Alzheim...mentioning
confidence: 99%
“…Transcranial photobiomodulation (tPBM) has emerged as a promising neurotherapeutic intervention, particularly for cognitive impairments caused by injury, infection and neurodegeneration [1][2][3][4] . Despite its potential, a significant gap exists in understanding the immediate electrophysiological effects of tPBM, particularly regarding optimal dosage parameters for effective treatment.…”
Section: Introductionmentioning
confidence: 99%
“…NIR transcranial treatment, also known as photobiomodulation (PBM) therapy, uses non-ionizing light sources such as lasers, LEDs, and broadband light in the visible and infrared range emitting NIR light (wavelengths between 800 and 2500 nm). If an optical window between 650 and 1200 nm is employed, the produced light can pass through the physical barriers of the skin and skull and reach the brain parenchyma [ 26 ]. It is a nonthermal process in which endogenous chromophores cause events at different biological scales.…”
Section: Introductionmentioning
confidence: 99%